Representation and disidentification in the testimony of a prostitute (Santiago de Chile, 1908) - Vera Gajardo, Antonieta; Sáez Baeza, Chiara (Arenal. Revista de historia de las mujeres, 2021)
From the feminist political theory, the present work develops an analysis around the struggle of a popular feminine subject for the power of (self)representation at the beginning of the 20th century. In particular, from the complaint —kept in the National Historical Archive of Chile— of María Espinoza against her ex-pimp, we identify and analyze the ploy and the disidentification as “outcast strategies” (Varikas, 2007). Focusing on the hermeneutic potential of these paradoxical political strategies, we develop a reading in contravention of this prostitute’s testimony in order to analyze certain marks of the gender historicity that contribute to construct critical genealogies of the legitimate femininity.